A Child's Journey to Recovery : Assessment and Planning with Traumatized Children. - Tomlinson, Patrick (Delivering recovery., 2007)
This book shows how carefully planned and assessed treatment can help traumatized children. It outlines how to set up a process for measuring a child's progress towards recovery. Uniquely, the book describes a practical outcomes-based approach that can be provided by an integrated multi-disciplinary team. Particular themes addressed include the conflict between the child's chronological and emotional ages, the need to work at the child's pace, the importance of the whole-team approach, and the challenges involved in measuring progress. The authors describe clearly defined outcomes for recover.